2018
DOI: 10.1177/2325967118s00143
|View full text |Cite
|
Sign up to set email alerts
|

Patellar Tendon Thickness and Failure After Anterior Cruciate Ligament Reconstructions with Bone-Patella Tendon-Bone Autograft

Abstract: Objectives:The purpose of this study was to determine if patellar tendon (PT) thickness measured on pre-operative magnetic resonance imaging (MRI) is a risk factor for failure after anterior cruciate ligament reconstruction (ACLR) using bone-patella tendon-bone (BTB) autograft.Methods:18 patients [age (mean 96 Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:”Table Normal”; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow: yes; ms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…found that BTB reconstruction failures were associated with significantly thicker patellar tendons at the inferior pole of the patella, likely indicative of preexisting patellar tendinopathy. 33 In a review of the New Zealand ACL Registry, Murgier et al. reported that, in skeletally mature patients under age 20 who had undergone ACL reconstruction with either HS or BTB autograft, BTB grafts had the largest mean diameter and lowest overall failure rate.…”
mentioning
confidence: 99%
“…found that BTB reconstruction failures were associated with significantly thicker patellar tendons at the inferior pole of the patella, likely indicative of preexisting patellar tendinopathy. 33 In a review of the New Zealand ACL Registry, Murgier et al. reported that, in skeletally mature patients under age 20 who had undergone ACL reconstruction with either HS or BTB autograft, BTB grafts had the largest mean diameter and lowest overall failure rate.…”
mentioning
confidence: 99%